AN ANALYSIS OF TRANSLATION PROCEDURES USEDIN COPYWRITING TRANSLATION(A Case Study of Advertising Headlines) - Ressa Ratna Daniar Soepandi, - (2011)
This study is entitled "An Analysis of Translation Procedures Used in Copywriting Translation (A Case Study of Advertising Headlines)". It aims to identify the translation procedures that are used in advertising headlines and to find out the most preferred translating advertising headlines according to the respondents. This research employed a qualitative case study. The study shows that there are 20 headlines to be analyzed in details. Several translation procedures were applied on the headlines: literal, reduction and expansion, shifts/transposition, synonymy and adaptation (other procedures). The translation procedures used in the study are proposed by Newmark (1988); The results of the analysis are as follow: literal (8 headlines), reduction and expansion (5 headlines), shifts/transposition (3 headlines), synonymy (1 headline), and adaptation (other procedures) (3 headlines). Literal is is the translation procedures that is mostly used. In terms of the most preferred headlines, they are Close-up (literal), Nippon paint (Shifts/Tranposition), Coca-cola (adaptation) Koko krunch (literal), Olay (synonymy). Headline that uses literal translation is the most preferred one. It is recommended that further study to be conducted to look more closely at the procedures of translation as well as other elements copywriting.